PROJE TABANLI İŞ BİRLİKLİ ÖĞRENMENİN ÖĞRENCİLERİN TÜRKÇE DERSİNDEKİ EKLER KONUSUNU ÖĞRENMELERİNE ETKİSİ. - VARIŞOĞLU, Behice; SEVİM, Oğuzhan (Journal of International Social Research / Uluslararası Sosyal Araştırmalar Dergisi, 2014)
The aim of this study is to investigate the effect of project based cooperative learning method on the success of Turkish student's affixes subject learning. In the study was used quasi-experimental design with control group, which was widely used in quantitative studies. The participants were 87 people that studiying at a secondary school in 6 grade A and B classroom at city centrum in Erzurum in Turkey (N= 45; N= 42). The data were gathered through success test that total 30 open-ended questions. In the analysis of the pre-test and post-test data t-test was used for independent-sample and dependent-sample. The study showed that the project based cooperative learning method is more effective than existing curriculum on the success of Turkish student's affixes subject learning.